Growth Promotion Effect Of Trichoderma Isolates On Tomato Seedlings (Journal of Plant Disease Sciences, 2019)
Trichoderma species are commonly used as biological control agents against phytopathogenic fungi and some isolates are able to improve plant growth also. The effects of five native isolates of Trichoderma harzianum along with Pusa strain Trichoderma asperellum in tomato seedling height, shoot fresh weight, shoot dry weight, root fresh weight and root dry weight were examined. Seed germination rate was not affected by Trichoderma application, but seedling height, shoot fresh weight, shoot dry weight, root fresh weight and root dry weight in tomato seedlings were increased when seed bioprimed with Trichoderma harzianum and T. asperellum strain compared to the control. Among the Trichoderma, T. asperellum obtained significantly increase in seedling height (12.10cm), shoot fresh weight (11.23g), shoot dry weight (1.25g), and root fresh weight (1.49g) and root dry weight (0.33g) as compare to other treatments.
Keywords: Trichoderma harzianum; T. asperellum; Growth promotion; and Bio-priming